Coffee variety, origin and extraction procedure: Implications for coffee beneficial effects on human health. (25th April 2019) - Ciaramelli, Carlotta; Palmioli, Alessandro; Airoldi, Cristina
Highlights: A method for rapid coffee metabolite determination from NMR spectra is described. Different coffee varieties, origins and extraction procedures are compared. Hydroalcoholic extraction is the most efficient in terms of LMW compounds' yield. The moka extraction affords the highest yields of melanoidins. Ratio between healthy compounds and caffeine is higher in Arabica coffees. Abstract: We set up an efficient protocol for the rapid analysis of NMR spectra of green and roasted coffee extracts, enabling the automatic identification and quantification of metabolites in approximately two minutes per spectrum. This method allowed for the metabolic profiling and the subsequent evaluation of the content of bioactive compounds and antioxidant activity of coffee samples, depending on their species (Arabica and Robusta), geographical origin and extraction procedure (hydroalcoholic, espresso and moka). The hydroalcoholic extraction is the most efficient method in terms of yields of low molecular weight compounds (in particular chlorogenic acids), while moka extraction provides the highest amounts of melanoidins. Moreover, that the ratio between health-giving compounds (chlorogenic acids, trigonelline and choline) and caffeine is higher in Arabica coffees. The data collected provide useful insights for the selection of coffee raw material to be used in the preparation of coffee-based dietary supplements, nutraceuticals and functional beverages.